Unlocking sorghum market opportunities in Benin - Anihouvi, Sèdo Eudes; Pede, Pénelope; Adinsi, Laurent; Hotegni, Francis; Honfozo, Laurenda; Bouniol, Alexandre; Tran, Thierry; Dufour, Dominique; Akissoe, Noël (CGIAR Science Program on Breeding for Tomorrow, 2025)
Sorghum is a key staple crop cultivated across the central and northern regions of Benin. It plays a vital role in ensuring food security, supporting rural livelihoods, and contributing to the agricultural economy. Despite its adaptability to diverse agroecological zones and its ranking as the third most important cereal crop after maize and rice, sorghum remains absent from the government’s list of priority crops. This brief draws on a synthesis of existing knowledge and stakeholder surveys involving farmers, traders, and consumers to identify the constraints and opportunities surrounding sorghum production and marketing in Benin. The findings reveal major challenges such as a lack of quality seed supply, limited extension services, and vulnerability to biotic and abiotic stresses. Farmers often rely on seeds from previous harvests or local markets, thus hindering the adoption of improved varieties. Economically, sorghum cultivation is more profitable than maize, with an opportunity cost advantage of approximately 54,000 FCFA (USD 108) per hectare. Market segmentation is emerging based on end-user preferences, ranging from red sorghum enthusiasts to a growing demand for white sorghum. This highlights untapped potential for targeted value chain development. To fully leverage sorghum’s potential, strategic interventions are needed in several areas: strengthening seed systems, improving access to extension services, enhancing institutional support, and developing structured market segments (as seen in successful rice, pineapple, and cashew sectors). By addressing production constraints and promoting climate-resilient varieties, sorghum can play a central role in boosting food security, nutrition, and economic resilience in Benin.